Ampullary Metastasis From Breast Cancer: A Rare Cause of Obstructive Jaundice - Giestas,Sílvia (2016)
Breast cancer is the most common tumor in women and the first cause of death for malignancy in the female. Bile ducts are not among the common sites of metastasis from breast cancer. Few cases of obstructive jaundice due to metastatic breast cancer have been described in the literature and they mostly resulted from widespread liver metastases that eventually involved the bile ducts. We report an exceptional case of ampullary metastasis in the absence of liver metastases. Sporadic reports have been published about the involvement of the ampulla by breast cancer metastasis. This case emphasizes the need to consider this diagnosis in women presenting with obstructive jaundice, especially when there is a clinical possibility of breast cancer.